2023
DOI: 10.1002/jcp.31168
|View full text |Cite
|
Sign up to set email alerts
|

AdipoRon reduces TGFβ1‐mediated collagen deposition in vitro and alleviates knee stiffness in vivo

Amel Dudakovic,
Afton K. Limberg,
Cole E. Bothun
et al.

Abstract: Arthrofibrosis, which causes joint motion restrictions, is a common complication following total knee arthroplasty (TKA). Key features associated with arthrofibrosis include myofibroblast activation, knee stiffness, and excessive scar tissue formation. We previously demonstrated that adiponectin levels are suppressed within the knee tissues of patients affected by arthrofibrosis and showed that AdipoRon, an adiponectin receptor agonist, exhibited anti‐fibrotic properties in human mesenchymal stem cells. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Our group recently investigated AdipoRon implementation in a mouse model of knee stiffness, and determined molecular and phenotypic evidence that AdipoRon mitigated contracture following serial dosing at 5 mg/kg for 6 weeks after contracture initiating surgery. 19 The early benefits of AdipoRon observed in the present investigation recapitulated these findings.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our group recently investigated AdipoRon implementation in a mouse model of knee stiffness, and determined molecular and phenotypic evidence that AdipoRon mitigated contracture following serial dosing at 5 mg/kg for 6 weeks after contracture initiating surgery. 19 The early benefits of AdipoRon observed in the present investigation recapitulated these findings.…”
Section: Discussionsupporting
confidence: 84%
“…[16][17][18] Importantly, recent studies have determined that AdipoRon impaired TGFβ1-induced fibrosis phenotype in mesenchymal progenitor cells and primary knee fibroblasts. 11,19 Notably, AdipoRon also improved knee passive extension in a mouse model of knee stiffness. 11,19 Furthermore, it was recently demonstrated that intravenous (IV) AdipoRon administration is safe in surgically stressed rabbits.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation